THE APPLICATION OF ENVIRONMENTAL ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY (CSR) IN IMPROVING FINANCIAL PERFORMANCE AMONG MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (BEI) IN THE YEAR 2025 - Surachman Surachman; Ibrohim Ibrohim (Yayasan Education and Social Center, 2026)
This study aims to analyze the application of environmental accounting and Corporate Social Responsibility (CSR) in improving financial performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the year 2025. The study employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, documentary observation, and analysis of annual reports and sustainability reports from three manufacturing companies in the basic and chemical industries, referred to as PT A, PT B, and PT C. Research informants included the Finance Manager, Chief Sustainability Officer (CSO), the Accounting Team, and the CSR Lead. Data analysis was conducted through data reduction, data presentation, conclusion, and triangulation of sources to ensure the credibility of the findings. The research results indicate that the companies have implemented environmental accounting through the recognition of environmental costs, investment in environmentally friendly technology, and the recording of waste management costs. CSR programs have also evolved from philanthropic activities towards a Creating Shared Value (CSV) approach focused on community empowerment and supply chain sustainability. The research findings indicate that the implementation of environmental accounting and CSR does not directly improve financial performance, but rather through enhanced operational efficiency, strengthened corporate reputation, increased investor confidence, and stable relationships with stakeholders. This research contributes to the development of sustainable accounting practices and guides companies in strengthening business strategies focused on sustainability and the creation of long-term value.